Factors influencing physical activity for hypertension prevention among older adults in a peri-urban community in Ho, Ghana - Kennedy Diema Konlan; Ruth Nimota; Mirialys Fiona Nana Ama Anaman; Anita Fafa Dartey; Elvis Reindolf Kale; Judith A. Anaman-Torgbor (PLoS ONE, 2025)
Background Regular physical activity is proven to be an effective risk-reduction strategy against hypertension among older adults. This study assessed the factors influencing regular physical activity among older adults in a peri-urban community. Methodology A cross-sectional study was conducted among 276 older adults aged 60 years and above, with or without hypertension, in the Ho Municipality. A convenience sampling method was employed for older adults to respond to a self-developed pretested questionnaire. Data was cleaned and analyzed using Statistical Package for Social Sciences (SPSS) and summarized using descriptive statistics, and chi-square tests of association. Variables found to be statistically significant ( p-value = 0.05) from the univariate analysis were modeled into a regression equation and reported as odds ratios. Findings The overall knowledge levels of the participants on regular physical activity showed a majority (57.6%) had low knowledge of regular physical activity, a significant association between the level of education (χ² = 8.518, p-value = 0.004), and the number of people in the household (χ² = 8.154, p-value = 0.043) with the level of knowledge. The results also showed that the majority (56.2%) of the participants self-reported low levels of regular physical activity. Participants between 60 to 64 years old had 4.740 times the odds of participating in physical activities than those aged above 80 years (AOR = 4.740, 95%CI:1.472–15.257 p-value = 0.009). The respondent’s level of education significantly predicted the likelihood of engaging in physical activity (AOR = 1.814, 95%CI:1.024–3.212, p-value = 0.041). Conclusion The reported low knowledge of physical activity among older adults highlights the importance of health education through leveraging community health workers and volunteers. Understanding specific barriers older adults face in engaging in physical activity, such as health concerns, lack of access to appropriate facilities, and cultural beliefs, may influence the strategic allocation of resources.